A Mighty Wind - Guest, Christopher; Belafsky, Marty, 1975-; Mary Gross; Michael Baser; Stuart Luce; Jim Moret (USA Castle Rock Entertainment, 2003)
When folk icon Irving Steinbloom passed away, he left behind a legacy of music and a family of performers he has shepherded to folk stardom. To celebrate a life spent submerged in folk, Irving's loving son Jonathan has decided to put together a memorial concert featuring some of Steinbloom's best-loved musicians. There's Mitch and Mickey, who were the epitome of young love until their partnership was torn apart by heartbreak
Mockumentary captures the reunion of 1960s folk trio the Folksmen (Guest, McKean, Shearer) as they prepare for a show at The Town Hall to memorialize a recently deceased concert promoter.
Language : English
Subtitles : English, Turkish, Serbo-Croatian, Estonian, Latvian, Lettish
Keywords: Music; Comedy